Determination of the absorbed dose to water in Cs-137 research irradiator chambers using Fricke dosimetry - Natasha Briggs; Andrea Mantuano Coelho da Silva; Arissa Pickler Oliveira; Domingos Cardoso D'Oliveira; Aneuri Souza de Amorim (Brazilian Journal of Radiation Sciences)
The IDQBRN/CTEx has a Cs-137 research irradiator whose prupose is to promove the development of research in the area of irradiation of materials, assisting in the acquisition of data and scientific publications in the area. Because it is used for research, it is necessary to verify the distribution of dose point in the irradiator chambers. The purpose of this work is to carry out a five-point dosimetry of each irradiator chamber, using the Fricke chemical dosimeter. This dosimeter is used worldwide in several areas of medical and industrial physics, presenting relevant characteristics such as low cost, uncertainties of less than 3% in industrial applications, in addition to being an absolute and primary dosimeter. Dosimetry was performed in the IDQBRN/CTEx irradiator drawers where the materials to be irradiated are placed in the research irradiator chamber.